2021
DOI: 10.1055/s-0040-1721622
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profiling and Trends of Primary Intracranial Tumors: A Hospital-Based Brain Tumor Registry from a Tertiary Care Center

Abstract: Background and Objectives Hospital-based cancer registry is an essential tool for augmentation of the standard of care, administration motive, and resource for population-based cancer registries. Here, we presented hospital-based brain tumor registry (HBBTR) to outline a comprehensive epidemiological data, both clinical and histopathological, as well as trends of central nervous system tumors. In addition, we compare this data with national brain tumor data as well as an international brain tumor registry. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(24 reference statements)
3
0
0
Order By: Relevance
“…The male:female ratio of incidence of primary brain tumours in the North-Eastern population was 2.3:1 [10] which is almost similar to that in our study (2.1:1). In a study of the Indian population, the frequency of brain tumours is highest in the 5th decade, while our study shows the frequency to be highest in the 4th decade [8]. The most common presenting symptom was headache (53%), followed by vomiting (28%), which is comparable to the study of Western population, where headache was the most common symptom [9,11].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The male:female ratio of incidence of primary brain tumours in the North-Eastern population was 2.3:1 [10] which is almost similar to that in our study (2.1:1). In a study of the Indian population, the frequency of brain tumours is highest in the 5th decade, while our study shows the frequency to be highest in the 4th decade [8]. The most common presenting symptom was headache (53%), followed by vomiting (28%), which is comparable to the study of Western population, where headache was the most common symptom [9,11].…”
Section: Discussionsupporting
confidence: 78%
“…In our study and that of the western population, supratentorial tumours predominate over infratentorial tumours [11]. In our study, it was found that Glioblastoma and Astrocytomas are the two most common primary brain tumours, while in both the Indian and Western populations, Meningioma and Glioblastoma are the most common primary brain tumours [8,12]. Ependymomas represented 3% of all intracranial neoplasms in this study, which is equal to that in an Indian study [8] and comparable to 2% in western studies [8,9].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation